Building and Sustaining a Community Advisory Board of African American Older Adults as the Foundation for Volunteer Research Recruitment and Retention in Health Sciences - Mitchell, Jamie (Ethn Dis, 2020)
Older African Americans’ participation in health-related research is severely limited; they are not involved in sufficient numbers to ensure the applicability of advancements in medical and behavioral health. This research participation gap exacerbates older African Americans’ vulnerability to poor health outcomes and disparities. The Michigan Center for Urban African American Aging Research employs a progressive community-based participatory model that utilizes a structured community advisory board (CAB) of African American older adults in metro Detroit, Michigan to oversee the research recruitment and retention of fellow minority older adult research participants. CAB members develop and support community health programming that provides free resources to older adults and also serves as fertile ground for recruiting participants in a volunteer research registry. CAB members are also provided ongoing training on social and behavioral health research and are supported in acting as a consultancy to outside researchers where they can be compensated for their expertise and engagement. This community-engaged model of sustaining a CAB of African American older adults offers key lessons learned on building relationships and trust, valuing and leveraging community members’ expertise and time, sharing decision-making, and fostering genuine community all while promoting research recruitment and retention among underserved populations.